Quand l’événement traumatique frappe au travail : une analyse du soutien social de l’entourage professionnel - Françoise Legros; Camila Carvallo (Perspectives Interdisciplinaires sur le Travail et la Santé)
There is, unfortunately, no zero risk with regard to the occurrence of traumatic events in the work place. When these events do occur, they can seriously affect the workers concerned. The moderating effect of social support on the traumatic events’ impact on workers is recognized in the literature; the fact that the caregivers’ good intentions are not enough to make their support fully effective is also recognized.This article analyzes the support needs of 41 workers affected by different traumatic events at work, the support provided by the professional team, and the workers’ perception as to how the support met their needs. The parameters of traumatic events show that workers' support needs remained stable. We also observed differences in how the different types of support and sources of support were perceived. In general, the respondents felt that the support that they received did not adequately meet their needs. These results provide opportunities for the development of preventive measures in companies, support for workers affected by traumatic work events, and, more specifically, avenues for implementing social support by professional teams.